2021
DOI: 10.32749/nucleodoconhecimento.com.br/psicologia/hospital-universitario
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de Burnout em profissionais de saúde em cenário de pandemia de Covid-19: análise de um hospital universitário

Abstract: Introdução: A Síndrome de Burnout (SB) ocorre quando há o esgotamento físico e emocional do trabalhador. Pesquisas demonstraram que as características do trabalho estão associadas ao desenvolvimento desta doença. A pandemia do coronavírus 2019 (COVID-19) foi responsável por estabelecer novos desafios para os profissionais de saúde relacionados ao surgimento de uma nova doença, como: cargas de trabalho prolongadas e sentimento de insegurança quanto a uma possível infecção pelo vírus. Questão norteadora: Qual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…It is worth noting that in this study, as in Barello et al (2020), Hu et al (2020) and Salviato and Vasconcelos Filho (2021), the EE dimension was observed as the majority manifestation. Interpersonal demands, work load and pressure are triggers for exhaustion.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…It is worth noting that in this study, as in Barello et al (2020), Hu et al (2020) and Salviato and Vasconcelos Filho (2021), the EE dimension was observed as the majority manifestation. Interpersonal demands, work load and pressure are triggers for exhaustion.…”
Section: Discussionsupporting
confidence: 54%
“…Research carried out in the Brazilian Southeast region identified that the nursing team had high EE (44.26%), high DE (56.61%) and low RP (27.22%) (Salviato & Vasconcelos Filho, 2021). In the present study, in turn, less expressive situations were identified, with 28.7% for high EE, 3.8% for high DE and 24.8% for low RP, which demonstrates different effects of the pandemic in different locations and periods.…”
Section: Discussionmentioning
confidence: 38%
See 2 more Smart Citations